2019
DOI: 10.1111/desc.12807
|View full text |Cite
|
Sign up to set email alerts
|

Brain lateralization of phonological awareness varies by maternal education

Abstract: Socioeconomic status (SES) has been shown to influence language skills, with children of lower SES backgrounds performing worse on language assessments compared to their higher SES peers. While there is abundant behavioral research on the effects of SES, whether there are differences in the neural mechanisms used to support language skill is less established. In this study, we examined the relation between maternal education (ME), a component of SES, and neural mechanisms of language. We focused on Kindergarte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…This finding is consistent with our prediction and prior work that showing significant and pronounced SES-related differences in verbal processing (e.g., Demir et al, 2015;Noble, Norman, & Farah, 2005). Previous neuroimaging studies suggest that the neural basis of verbal processing, specifically the left IFG, is more specialized in higher SES children (Hackman & Farah, 2009;Raizada et al, 2008;Younger et al, 2019). Children's early experiences might account for the observed differences underlying reasoning.…”
Section: Parental Education Correlates With Verbal Neurocognitive Systems That Underlie Reasoningsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with our prediction and prior work that showing significant and pronounced SES-related differences in verbal processing (e.g., Demir et al, 2015;Noble, Norman, & Farah, 2005). Previous neuroimaging studies suggest that the neural basis of verbal processing, specifically the left IFG, is more specialized in higher SES children (Hackman & Farah, 2009;Raizada et al, 2008;Younger et al, 2019). Children's early experiences might account for the observed differences underlying reasoning.…”
Section: Parental Education Correlates With Verbal Neurocognitive Systems That Underlie Reasoningsupporting
confidence: 92%
“…Functional neuroimaging studies using language tasks reveal similar SES-related differences (Romeo et al, 2018;Younger, Lee, Demir-Lira, & Booth, 2019). For example, Raizada, Richards, Meltzoff, and Kuhl (2008) found that the asymmetry in the activity of the left perisylvian regions during a rhyming task-related to the maturation of language processing-was less pronounced in children from disadvantaged SES backgrounds compared with those from more advantaged SES backgrounds.…”
Section: Ses-related Differences In the Verbal And Nonverbal Systems In The Brainmentioning
confidence: 91%
“… Tong et al (2016) showed that selecting the top activated voxels for each individual within an anatomical ROI as compared to other methods was more sensitive in finding group differences. In addition to our current study, several previous studies have also used this approach to examine brain-behavioral correlations ( Suárez‐Pellicioni and Booth, 2018 ; Younger et al, 2019 ; Wang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, SES disadvantage has been associated with reduced volume (e.g., Jednoróg et al, 2012 ; Hair et al, 2015 ), thickness ( Mackey et al, 2015 ), and surface area ( Noble et al, 2015 ) in cortical regions underlying language comprehension, including perisylvian areas (e.g., STG) and ventrolateral prefrontal areas (e.g., IFG; Noble et al, 2012 ; Piccolo et al, 2016 ). SES-related differences are also observed in white matter structures, and in functional brain systems, involved in language processing ( Raizada et al, 2008 ; Gullick et al, 2016 ; Younger et al, 2019 ). However, parental SES is a complex construct of many components (e.g., parental income, education, and neighborhood characteristics).…”
Section: Parental Language Input and Brain Areas Associated With Language Developmentmentioning
confidence: 99%